PENGARUH VARIASI KONDISI FERMENTASI TERHADAP PRODUKSI METABOLIT ANTIBAKTERI EKSTRAK ISOLAT I5 FUNGI ENDOFIT Anredera cordifolia (Ten.) Steenis - Ismail Ismail; Megawati Megawati; Alimuddin Ali; Fuji Asmiati Ningsih (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2019)
Endophytic fungi are one of the microorganisms that live in plants and symbiotic with their host plant produce secondary metabolites. This study aims to determine the optimum growth profile of endophytic fungus isolated from the leaf of Anredera cordifolia (Ten.) Steenis namely isolate I5 as antibacterial. The fungus growth profile optimization analyzed by a correlation between fermentation time and mycelium weight, which collected every 24 hours for 15 days. The media were varied at pH conditions of 4, 7, and 8 in each PDYB medium (glucose and fructose substrates). The results showed that isolate I5 grew optimally on the 13th day on the PDYB medium pH 8. Ethyl acetate extract 5% of isolate I5 could inhibit bacteria growth with the largest inhibition zone diameter against Staphylococcus aureus of 9.96 mm (± 0.60) and Escherichia coli of 9.03 mm (± 0.46).